Analysis Of The Implementation Of Government Regulation Number 47 Of 2021 Concerning The Organizer Of The Hospitalization Sector At The Jimmy Medika Mother And Child Hospital Borneo Samarinda - dwi ida puspitasari; Ulia Fitri; Sumarni Sumarni (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2022)
A hospital is a health service institution that provides plenary individual health services that provide inpatient, outpatient, and emergency services. The purpose of this study is to analyze the implementation of Government Regulation Number 47 of 2021 concerning the Operator of the Hospitality Sector at RSIA JMB Samarinda. This study uses a qualitative research design to implement Government Regulation Number 47 of 2021 concerning the Organizer of the Hospitality Sector at RSIA Jimmy Medika Borneo. Based on the results of research and discussion, it is concluded that the services that have not been fulfilled are medical rehabilitation services, buildings and infrastructure that have not been met are the High Care Unit (ICU) inpatient room and radiology room, the availability of unfulfilled beds is ICU equipment, isolation room equipment, and radiology room equipment, Human resources that have not been met are radiographers. The recommendations offered by this aspect of management policy, especially related to policy commitments in order to emphasize the policies that have been implemented in PP No. 47 of 2021 concerning the implementation of the hospitality sector, for health facilities and supporting facilities to be fulfilled immediately so that performance can be effective, related to human resources are expected to be added as soon as possible so that training can be carried out for all officers related to performance and critical thinking.